(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Anti-Epileptic Drugs (AEDs) are the primary therapeutic modes forepileptic patients and have been demonstrated to control seizure, which decreasesmorbidity and mortality associated with epilepsy. There is a paucity of data on drugadherence and seizure control status among epileptic patients in Bangladesh. Theaim of this study was therefore to assess adherence among epileptic patients and tosee association between adherence and control of seizures. Methods and materials: A cross-sectional observational study was conductedamong 253 patients who visited into outdoor and admitted inindoor of Neurologyand Medicine Department of Chattogram Medical College Hospital (CMCH) with aclinical diagnosis of epilepsy. Epileptic Patients who had taken AED for at least oneyear or more were recruited in the study to evaluate adherence and seizure controlthrough patient interview. Factors affecting adherence were determined usingregression analysis. Results: 38.8% patients were adherent to their treatment and only 33.6% of thepatients had controlled seizure, forgetfulness (35%) was the most reason for nonadherence.Monontherapy was commonly (72.7%) used, among which Valproic acidwas the most commonly utilized (30.4%) single anticonvulsant drug. Many factorswere affecting patient’s adherence such as socio-demographic related factors (age,education, occupation), therapy related factors and cost. Adherence to AED wasfound to have a significant association with seizure control status. Conclusions: The rate of adherence observed in this study was low. The mostcommon reason for nonadherence was forgetfulness. The findings indicate thatadherence was associated with well seizure control. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 68-73